Evaluation of functional capacity and risk of depression in older patients with cancer as part of the comprehensive geriatric assessment - Fidecki, Wiesław; Przylepa, Katarzyna; Wytrzyszczewski, Marek; Wysokiński, Mariusz (Frontiers in Aging Neuroscience, 2025)
BackgroundThe patient’s somatic health status plays an important role in the factors predisposing to the development of depression. Any disease, especially a chronic one, often associated with pain, may contribute to the development of depression. The aim of the study was to assess the impact of functional capacity on the occurrence of depression among elderly cancer patients.MethodsThe work used the diagnostic survey method and survey technique research tool consisted of standardized questionnaires: the Nurses’ Observation Scale for Geriatric Patients (NOSGER), the Barthel scale, and the Geriatric Depression Scale (GDS). The authors conducted the study among 110 older adults patients with hospitalized at the Lublin Region Oncology Center in 2022.ResultsWhen assessing patients using the NOSGER scale, the average result for the entire group was 45.98 ± 12.58 points. The examined people functioned best in terms of memory - average of 5.99 ± 1.32 points. The worst functioning was in the instrumental activities of everyday life - average 9.16 ± 3.61 points. In the assessment of the functional status using the Barthel scale, 54.54% of the respondents were classified as light. Based on the assessment of patients using the GDS scale, it was found that as many as 66.36% of the respondents did not experience symptoms of depression. The regression model showed that the NOSGER scale was a statistically significant variable explaining the geriatric depression scale score in the study group (p < 0.001).ConclusionMost respondents were fully functional. The surveyed seniors suffering from cancer had the greatest difficulties in the areas of moods and emotions as well as instrumental activities of everyday life. The occurrence of depression symptoms was found in over 30.00% of respondents. It is advisable to use research tools that take into account a wider range of aspects when assessing the impact of functional capacity on the possibility of depression among geriatric patients with cancer.